RESPON PETANI TERHADAP PELAKSANAAN PROGRAM ELECTRIFYING AGRICULTURE SUPER PANEN (STUDI KASUS PETANI LAHAN PASIR KALURAHAN SRIGADING KAPANEWON SANDEN KABUPATEN BANTUL) - Rahma Alfiani; Siti Hamidah (Agros Journal of Agriculture Science, 2023)
Program (2) examine farmers' responses to the implementation of the Electrifying Agriculture Super Harvest Program. This research is a qualitative research with the type of case study research with the subject of key informants, main, and supporting research using purposive sampling technique. Using primary data sources and secondary data sources with data collection techniques in the form of observation, interviews, and documentation. Data validity using source triangulation validity. The results showed that (1) The implementation of the Electrifying Agriculture Super Harvest Program consists of planning, implementation, evaluation, and program sustainability activities (2) The response of farmers to the implementation of the Electrifying Agriculture Super Harvest Program is dominated by the response to accept the implementation of this program farmers understand related information and program flow, feel helped in reducing operational costs, increasing security, the amount of fuel is stable, cheaper and more efficient, and can develop agriculture, while the rejection of the program is due to issues that cannot be separated from electrical energy including tariff increases, power outages, and differences in the timing of the installation of new customers in the third stage. INTISARIPenelitian ini bertujuan untuk (1) mengkaji pelaksanaan Program Electrifying Agriculture Super Panen (2) mengkaji  respon petani terhadap pelaksanaan Program Electrifying Agriculture Super Panen. Penelitian ini merupakan penelitian kualitatif dengan jenis penelitian studi kasus dengan subyek informan kunci, utama, dan pendukung penelitian menggunakan teknik purposive sampling. Menggunakan sumber data primer dan sumber data sekunder dengan teknik pengumpulan data berupa observasi, wawancara, dan dokumentasi. Keabsahan data menggunakan validitas triangulasi sumber. Hasil penelitian menunjukkan bahwa (1) Pelaksanaan Program Electrifying Agriculture Super Panen terdiri dari kegiatan perencanaan, pelaksanaan, evaluasi, dan keberlanjutan program (2) Respon petani terhadap pelaksanaan Program Electrifying Agriculture Super Panen didominasi respon menerima pelaksanaan program ini petani memahami terkait informasi dan alur program, merasa terbantu dalam menekan biaya operasional, meningkatkan keamanan, jumlah bahan bakar stabil, lebih murah dan hemat, lebih efisien, dan dapat mengembangkan pertanian, sedangkan penolakan program dikarenakan persoalan yang tidak dapat dipisahkan dari energi listrik meliputi kenaikan tarif, pemadaman listrik, dan perbedaan waktu pelaksanaan pemasangan pelanggan baru pada tahap ketiga.